Fluid Redistribution in Sleep Apnea: Therapeutic Implications in Edematous States - Silva, Bruno Caldin da; Kasai, Takatoshi; Coelho, Fernando Morgadinho; Zatz, Roberto; Elias, Rosilene M. (Frontiers in Medicine, 2018)
Sleep apnea (SA), a condition associated with increased cardiovascular risk, has been traditionally associated with obesity and aging. However, in patients with fluid-retaining states, such as congestive heart failure and end-stage renal disease, both prevalence and severity of SA are increased. Recently, fluid shift has been recognized to play an important role in the pathophysiology of SA, since the fluid retained in the legs during the day shifts rostrally while recumbent, leading to edema of upper airways. Such simple physics, observed even in healthy individuals, has great impact in patients with fluid overload. Correction of the excess fluid volume has risen as a potential target therapy to improve SA, by attenuation of nocturnal fluid shift. Such strategy has gained special attention, since the standard treatment for SA, the positive airway pressure, has low compliance rates among its users and has failed to reduce cardiovascular outcomes. This review focus on the pathophysiology of edema and fluid shift, and summarizes the most relevant findings of studies that investigated the impact of treating volume overload on SA. We aim to expand horizons in the treatment of SA by calling attention to a potentially reversible condition, which is commonly underestimated in clinical practice.